Molecular profile of 5-fluorouracil pathway genes in colorectal carcinoma - Kunicka, T; Prochazka, P; Krus, I; Bendova, P; Protivova, M; Šůsová, Simona; Hlaváč, Viktor; Liška, Václav; Novak, P; Schneiderová, Michaela; Pitule, Pavel; Brůha, Jan; et al. (BMC cancer, 2016)
BACKGROUND: This study addresses involvement of major 5-fluorouracil (5-FU) pathway genes in the prognosis of colorectal carcinoma patients. METHODS: Testing set and two validation sets comprising paired tumor and adjacent mucosa tissue samples from 151 patients were used for transcript profiling of 15 5-FU pathway genes by quantitative real-time PCR and DNA methylation profiling by high resolution melting analysis. Intratumoral molecular profiles were correlated with clinical data of patients. Protein levels of two most relevant candidate markers were assessed by immunoblotting. RESULTS: Downregulation of DPYD and upregulation of PPAT, UMPS, RRM2, and SLC29A1 transcripts were found in tumors compared to adjacent mucosa in testing and validation sets of patients. Low RRM2 transcript level significantly associated with poor response to the first-line palliative 5-FU-based chemotherapy in the testing set and with poor disease-free interval of patients in the validation set irrespective of 5-FU treatment. UPP2 was strongly methylated while its transcript absent in both tumors and adjacent mucosa. DPYS methylation level was significantly higher in tumor tissues compared to adjacent mucosa samples. Low intratumoral level of UPB1 methylation was prognostic for poor disease-free interval of the patients (P = 0.0002). The rest of the studied 5-FU genes were not methylated in tumors or adjacent mucosa. CONCLUSIONS: The observed overexpression of several 5-FU activating genes and DPYD downregulation deduce that chemotherapy naïve colorectal tumors share favorable gene expression profile for 5-FU therapy. Low RRM2 transcript and UPB1 methylation levels present separate poor prognosis factors for colorectal carcinoma patients and should be further investigated.
Keywords: regulace genové exprese u nádorů; ribonukleosiddifosfátreduktasa; kolorektální nádory; Antimetabolites, Antineoplastic; Female; Fluorouracil; CpG ostrůvky; ženské pohlaví; Gene Expression Regulation, Neoplastic; Colorectal Neoplasms; lidé; staging nádorů; Neoplasm Grading; signální transdukce; Aged, 80 and over; stanovení celkové genové exprese; metylace DNA; Signal Transduction; CpG Islands; Ribonucleoside Diphosphate Reductase; stupeň nádoru; Male; fluoruracil; Aged; protinádorové antimetabolity; DNA Methylation; lidé středního věku; transkriptom; senioři nad 80 let; senioři; mužské pohlaví; promotorové oblasti (genetika); Promoter Regions, Genetic; Transcriptome; Middle Aged; Neoplasm Staging; Gene Expression Profiling; Humans